Gating and permeation properties of two types of calcium channels in neuroblastoma cells. - Yoshii, M (1988)
The gating and permeation properties of two types of calcium channels were studied in the neuroblastoma cell line N1E-115. Calcium channel currents as carried by Ba2+ (50 mM) were recorded using the whole-cell variation of the patch electrode voltage-clamp technique. The two types of calcium channels showed similar membrane potential dependence with respect to the steady-state activation and inactivation gating properties. However, the properties of the long-lasting type II channels were shifted approximately 30 mV in the depolarizing direction compared with those of the transient type I channels. Activation of type I channels developed with a sigmoidal time course which was described by m2 kinetics, whereas the activation of type II channels was described by a single exponential function. Tail current upon repolarization followed an exponential decay in either type of calcium channels. In comparison to type I channels, the activation process of type II channels was shifted approximately 30 mV in the positive direction, while the deactivation process showed a 60 mV shift in the positive direction. The rate constants of activation obtained from the activation and deactivation processes indicated that under comparable membrane potential conditions, type II channels close 2.4 times faster than type I channels upon repolarization. When external 50 mM Ba2+ was replaced with Ca2+ or Sr2+ on the equimolar basis, the amplitudes of transient and long-lasting currents were altered without a significant change in their time courses. The ion permeability ratios determined from the maximum amplitude of the inward current were as follows: Ba2+ (1.0) = Sr2+ (1.0) greater than Ca2+ (0.7) for type I channels, and Ba2+ (1.0) greater than Sr2+ (0.7) greater than Ca2+ (0.3) for type II channels. Replacement of Ba2+ with Ca2+ caused a 10-12 mV positive shift in the current-voltage relation for type II channels. However, the shift for type I channels was much less. This suggests that negative surface charges are present around type II channels. After correction for the surface charge effect on the ion permeation, there was no significant difference between the permeability ratios of these cations for the two channel types. It was concluded that the two types of calcium channels have many common properties in their gating and permeation mechanisms despite their differential voltage sensitivity and ion selectivity.